ANALISIS FAKTOR MOTIVASI TANGGUNG JAWAB, PENGHARGAAN, DAN PRESTASI TERHADAP KEPUASAN KERJA PERAWAT RSUD RANTAUPRAPAT - Elma; Chrismis Novalinda; Ginting, Johannes Bastira (Ibnu Sina: Jurnal Kedokteran dan Kesehatan - Fakultas Kedokteran Universitas Islam Sumatera Utara, 2025)
Job satisfaction is an important factor that influences nurses' performance and the quality of health services. This study aims to explore the relationship between responsibility, reward, and achievement on nurses' job satisfaction at RSUD Rantauprapat. A quantitative research method with a descriptive approach was used, involving 175 respondents selected through purposive sampling. Results showed that 88% of nurses with high responsibility were satisfied, compared to 2% at low responsibility (p-value 0.001). Rewards also contributed significantly, with 86% of rewarded respondents reporting satisfaction (p-value 0.000). On the other hand, of the 130 nurses who felt accomplished, 70% were satisfied (p-value 0.002). Logistic regression analysis showed responsibility had the greatest influence on job satisfaction (Exp(B) = 8.833). This finding indicates that increasing nurses' sense of responsibility, reward, and recognition of achievement can improve job satisfaction, which in turn improves the quality of health services in the hospital